Directionally enhanced probe for side‐illumination Tip enhanced spectroscopy. (3rd June 2016) - Shen, Hongming; Lu, Guowei; Cao, Zhengmin; He, Yingbo; Cheng, Yuqing; Li, Jiafang; Li, Zhi‐Yuan; Gong, Qihuang
Abstract : We investigate the high performance of an apertureless near‐field probe consisting of a tapered metal tip with periodic shallow surface grooves. The spontaneous emission of a single emitter near the apex is systematically analyzed for side‐illumination tip enhanced spectroscopy scheme. In contrast to a conventional bare tapered tip, the corrugated probe not only strongly enhances the local excitation field, but also modulates the emission directivity, leading to high collection efficiency and signal‐to‐noise ratio. Specifically, we propose that an asymmetric tip enhanced spectroscopy probe containing two different length nanorods at the apex realizes unidirectional emissions. The radiation pattern is sensitive to the emission wavelengths and the emitter positions, which can increase the signal‐to‐noise ratio through suppression of the undesired signal. The proposed asymmetrical corrugated probe possesses a wide range of potential applications, including increasing the detection efficiency of tip enhanced spectroscopy at the single molecule level. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Directional and enhanced spontaneous emission controlled by an asymmetric corrugated metal probe is proposed and demonstrates improved detection efficiency of tip enhanced spectroscopy.